Understanding how emotional intelligence shapes teachers’ reflective and creative teaching: the moderating role of teacher autonomy - Orakci, Şenol; Aktan, Osman; Çevik, Hüseyin (Frontiers in Psychology, 2026)
IntroductionEmotional intelligence is a key predictor of teachers’ instructional behaviors, yet its role in shaping reflective and creative teaching remains insufficiently understood. Little evidence explains how emotional intelligence promotes creative teaching through reflective practice or how teacher autonomy conditions this process. This study examines a moderated mediation model linking emotional intelligence, reflective teaching, creative teaching, and teacher autonomy.MethodsUsing a cross-sectional survey design, data were collected from 690 teachers in 78 schools across 24 Turkish cities. Validated scales measured emotional intelligence, reflective teaching, creative teaching, and autonomy. Multilevel structural equation modeling with Bayesian estimation tested indirect and moderated effects.ResultsEmotional intelligence showed a significant indirect effect on creative teaching through reflective teaching. Teacher autonomy strengthened this indirect pathway, amplifying the positive influence of emotional intelligence on reflection and, in turn, creative instruction.DiscussionFindings highlight the central roles of emotional intelligence, reflective practice, and autonomy in fostering creative teaching. Enhancing teachers’ emotional skills, reflective capacities, and autonomy may support more innovative instructional practices and improved learning outcomes.